Malignant transformation of kissing nevus- a rare entity - Kharel, R Sitaula; Bhatta, S; Shrestha, G B; Shrestha, J K (Nepalese Journal of Ophthalmology, 2012)
Background: Kissing nevus is a congenital nevus in adjacent parts of the eyelids. Malignant transformation of kissing or divided nevi of the eyelids is rarely described. Objective: To report a very rare case of malignant transformation of kissing nevus with ocular and extraocular spread. Case: A 57- year- old man with 6/6 visual acuity in both eyes presented with a kissing nevus present since birth in right upper and lower eyelids which had a slow growth phase. The upper lid in the area of the nevus was thickened with a 20x12x15 mm black pigmented crusted hemorrhagic nodular lesions. The lower lid had a 6 mm black pigmented ulcerated lesion over the pre-existing nevus in the lateral third of the lid with full thickness infiltration. Another 5x4 mm pigmented lesion over the lower medial lid margin with a thickness of about 3 mm extended to the conjunctival side of the lower lid. Right sided pre-auricular and submaxillary nodes were palpable. A biopsy of tissue samples from the eyelid and pre-auricular nodes were consistent with malignant melanoma.Conclusion: Malignant transformation of kissing nevus is rare. It can spread to the conjunctiva, pre-auricular and sub-mandibular lymphnodes.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6555 Nepal J Ophthalmol 2012; 4 (2): 329-332